Privatization in Eastern Germany: Management Selection and Economic Transition - Dyck, I. J. Alexander (American Economic Review, 1997)
This paper suggests that management's role in enterprise restructuring and market failures in the managerial labor market help explain important features of the German privatization program. A model of adverse selection based on information advantages for private owners demonstrates how privatization can improve the quality and number of western managers in eastern enterprises. These benefits can increase with the size of the transition. Evidence of management replacement and significant differences between state-owned and privatized firms from a survey of eastern German firms supports model assumptions and predictions. These results suggest the importance of management replacement to successful privatization. Copyright 1997 by American Economic Association.